2009
DOI: 10.1007/s12603-009-0104-z
|View full text |Cite
|
Sign up to set email alerts
|

What is a meaningful change in physical performance? Findings from a clinical trial in older adults (the LIFE-P study)

Abstract: Objective Performance measures provide important information, but the meaning of change in these measures is not well known. The purpose of this research is to 1) examine the effect of treatment assignment on the relationship between self-report and performance; 2) to estimate the magnitude of meaningful change in 400-meter walk time (400MWT), 4-meter gait speed (4MGS), and Short Physical Performance Battery (SPPB) and 3) to evaluate the effect of direction of change on estimates of magnitude. Design This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
332
7
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(372 citation statements)
references
References 24 publications
26
332
7
7
Order By: Relevance
“…31,[42][43][44][45][46][47][48] Criteria for small and substantial meaningful change scores have been established. 49,50 Baseline SPPB scores in men with PCa suggest normally functioning individuals (scores greater than 9 out of 12 possible), but with a tendency for men with longer ADT exposure to have slightly lower scores compared with control groups. Notably, one cross-sectional study reported an SPPB score of 7.9 in men averaging 36 months of ADT.…”
Section: Sppbmentioning
confidence: 99%
See 2 more Smart Citations
“…31,[42][43][44][45][46][47][48] Criteria for small and substantial meaningful change scores have been established. 49,50 Baseline SPPB scores in men with PCa suggest normally functioning individuals (scores greater than 9 out of 12 possible), but with a tendency for men with longer ADT exposure to have slightly lower scores compared with control groups. Notably, one cross-sectional study reported an SPPB score of 7.9 in men averaging 36 months of ADT.…”
Section: Sppbmentioning
confidence: 99%
“…This .1 point difference from baseline is suggestive of a substantial meaningful change. 49,50 Men who had an average of 4 months of ADT at baseline as well as men with PCa not receiving ADT or HC changed by 0.42 and 0.17 points in SPPB, respectively, over the 24-month study period. Neither baseline values nor changes after 24 months were significantly different between groups.…”
Section: Sppbmentioning
confidence: 99%
See 1 more Smart Citation
“…We regarded as clinically relevant a difference of the SPPB score equal or greater than 1 point, which is considered a substantial change in the pertinent literature [21,22].…”
Section: Outcomementioning
confidence: 99%
“…We therefore suggest reporting mean ± SD/SE as a standard minimum. Relative changes may be reported, to further contextualise findings in relation to a minimum meaningful change from baseline [91]. Regarding the minimum meaningful change, it may be useful to refer to the critical difference of sa-T and sal-C to determine whether changes observed are biologically meaningful [79,145].…”
Section: Reviewmentioning
confidence: 99%